Preparation and evaluation of β-cyclodextrin functionalized periodic mesoporous organosilica open tubular capillary columns. Issue 28 (5th July 2017) - Guo, Dongqiang; Liu, Mingxia; Zhong, Shangwei; Dong, Yalei; Li, Xiangjun
Abstract : This study describes the preparation and electrochromatographic application of a chiral β-cyclodextrin functionalized periodic mesoporous organosilica bonded open tubular capillary column. Abstract : This study describes the preparation and electrochromatographic application of a chiral β-cyclodextrin functionalized periodic mesoporous organosilica bonded open tubular capillary column. The stationary phase (β-cyclodextrin functionalized period mesoporous organosilica; CD-PMO) was synthesized from bis(triethoxysilyl)ethane and N -[3-(trimethoxysilyl) propyl]ethylenediamine, followed by amino functionalization. The prepared CD-PMO was attached on the inner wall, which was modified by (3-glycidoxypropyl) methyldiethoxysilane, through a covalent bond. The stationary phase was characterized by Fourier-transform infrared (FT-IR) spectroscopy, Brunauer–Emmett–Teller (BET), and scanning electron microscopy (SEM). The electrochromatographic characterization of the stationary phase was performed using amino acid enantiomer derivatives. The effect of buffer pH and concentration on enantio-separation performance was also investigated. Good repeatability was gained, with relative standard deviation of the migration time and peak areas of less than 2.3% for run-to-run ( n = 5), 4.0% for day-to-day ( n = 5), and 5.0% for column-to-column ( n = 3).